Deep learning-based image denoising method - Chaitanya, Nosina Krishna; Sathukumati, Leela Lakshmi; Purini, Kalyani (Science, Engineering and Health Studies, 2025)
Image denoising is crucial in image processing and computer vision. Noise present in digital images captured by cameras, smart phones, and other devices can severely degrade image quality and negatively impact image-based tasks such as object recognition and image segmentation. Image-denoising algorithms aim to remove the noise from the images while preserving their key features. Deep learning-based methods have demonstrated better performance than conventional ones. In light of these developments, a novel image-denoising method was proposed based on a deep neural network that utilizes both residual connections and attention mechanisms. This method was trained on a large dataset of noisy and clean images to learn the mapping between the two. This technique achieved state-of-the-art denoising performance on various benchmarks and exhibited excellent generalization capability to real-world noisy images. In addition, it was computationally efficient and could process high-resolution images in real time.